Dietary curcumin supplementation attenuates inflammation, hepatic injury and oxidative damage in a rat model of intra-uterine growth retardation. Issue 5 (25th July 2018) - He, Jintian; Niu, Yu; Wang, Fei; Wang, Chao; Cui, Tao; Bai, Kaiwen; Zhang, Jingfei; Zhong, Xiang; Zhang, Lili; Wang, Tian
Abstract: Rats with a normal birth weight (NBW) or intra-uterine growth retardation (IUGR) were fed basic diets (NBW and IUGR groups) or basic diets supplemented with curcumin (NC and IC groups) from 6 to 12 weeks. The body weight of IUGR rats was lower ( P <0·05) than that of the controls. Rats with IUGR showed higher ( P <0·05) concentrations of TNF- α, IL-1 β and IL-6; higher ( P <0·05) activities of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) in their serum; and increased ( P <0·05) concentrations of malondialdehyde (MDA), protein carbonyl (PC) and 8-hydroxy-2'-deoxyguanosine (8-OHDG) in the liver compared with the NBW rats. The livers of IUGR rats exhibited a lower ( P <0·05) superoxide dismutase activity and decreased ( P <0·05) metabolic efficiency of the hepatic glutathione redox cycle compared with those of the NBW rats. In response to dietary curcumin supplementation, concentrations of inflammatory cytokines and activities of AST and ALT in the serum and MDA, PC and 8-OHDG in the liver were lower ( P <0·05), and the hepatic glutathione redox cycle in the liver was improved ( P <0·05) in the IC group than in the IUGR group. These results were associated with lower ( P <0·05) phosphorylated levels of the NF- κ B pathway and Janus kinase 2 (JAK2) and higher ( P <0·05) mRNA expression of genes involved in the nuclear factor, erythroid 2-like 2 ( Nfe2l2 )/antioxidant response element ( ARE ) pathway in the liver of the IC rats than that of the IUGR rats. Maternal undernutrition decreased birth weight and led to inflammation, oxidative damage and injury in rats. Curcumin appeared to be beneficial in preventing IUGR-induced inflammation, oxidative damage and injury by activating the expression of the NF- κ B, JAK/STAT and Nfe2l2 / ARE pathways in the liver.